2018
DOI: 10.1111/ctr.13342
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the enhanced recovery after surgery protocol in living liver donors

Abstract: Enhanced recovery after surgery protocol was effective in minimizing postoperative pain and helped to decrease the postoperative narcotics and helped early recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(67 citation statements)
references
References 7 publications
0
67
0
Order By: Relevance
“…First, our institution implements a robust perioperative pain management program that incorporates an ERAS protocol, which emphasizes multimodal analgesia. This protocol effectively controls pain and promotes early recovery in many surgical patients, including those undergoing urologic procedures 9,16,17 . Our institution's ERAS protocol includes encouraging regular activity and good nutrition preoperatively, clear liquids up to 3 hours before surgery, and gabapentin and acetaminophen in the preoperative holding area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, our institution implements a robust perioperative pain management program that incorporates an ERAS protocol, which emphasizes multimodal analgesia. This protocol effectively controls pain and promotes early recovery in many surgical patients, including those undergoing urologic procedures 9,16,17 . Our institution's ERAS protocol includes encouraging regular activity and good nutrition preoperatively, clear liquids up to 3 hours before surgery, and gabapentin and acetaminophen in the preoperative holding area.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we had previously demonstrated that the quantity of opioids patients consumed after these surgeries was significantly less than the quantity used 8 . Third, the majority of patients undergoing these surgeries participated in a specific ERAS protocol aimed at minimizing the use of perioperative opioids, among other things 9 . Prostatectomies included those performed through a traditional open approach (with a lower midline incision) or a minimally invasive approach (robotically).…”
Section: Methodsmentioning
confidence: 99%
“…(ERAS) to achieve early extubation, early functional exercise, and a shortened length of stay at the hospital 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Multimodal analgesic regime minimising opioid use has been shown to enhance recovery 2 30. ITM has become a well-documented component in several ERAS protocols29 31–34 and a protocol for a systematic review of ITM in abdominal and thoracic surgery patients has recently been published 35. Despite the higher rating of NRS at mobilisation during the first few days in the ITM group, the consumption of opioids was nearly three times lower in the same time period compared with the EDA group, and the QoL index did not differ between the groups.…”
Section: Discussionmentioning
confidence: 99%